ISLAM AND INTELLIGENCE: THE ISSUES OF FAITH AND INTELLECT - Siti Noor Mawar Abdul Rahman; Shereeza Mohamed Saniff (Journal of Islamic, Social, Economics and Development, 2020)
Spiritual intelligence is a concept in human intelligence studies based on secularism approach that separates intellect with religious faith. However, it has attracted many faith-based researchers, especially among Muslim scholars and researchers, in discussing the concept and issues of spiritual intelligence. This paper aims to discuss the polemic between faith and intellect in secularism as well as the influence it has brought to Islam using a descriptive research methodology. Based on the review of literatures, the data collected on secularism, faith and intellect were then analysed by means of content analysis. The findings suggest that although secularism advocates the separation of faith and intellect, nonetheless secularism has its own pseudo-religion indentity in the form of spiritual intelligence. The implications from the findings of this paper suggests that research of human intelligence from Islamic perspectives should embark on clear Islamic paradigm rather than from the secular human intelligence paradigm.